The Role of Remote Sensing in Forest Cover Changes in Butambala District, Central Uganda - Namayengo, Sarah; Nuwagira, Upton (East African Nature and Science Organization, 2024)
Natural forests in Uganda have experienced changes which must be quantified to inform future forest resource management and avoid the danger of reduced ecosystem service benefits. The primary purpose of this study was to assess forest changes in Butambala District by employing remote sensing techniques and GIS tehniques. The original contribution is the capacity to detect Central Forest Reserve cover decline using remote sensing in the study area for a 27-year period (1995-2020). Landsat 5 and Sentinel 2 images were processed using a supervised image classification approach to identify and quantify land use/cover changes. The study results indicated that the district has undergone land cover/use changes over the last 27 years. The prevailing changes in the district from 1995 to 2022 were expansions of built-up areas from (0.54% to 4.22%), agriculture from (42.38% to 79%), and decreases in grassland from (29.9% to 0%), natural forest cover from (14.07% to 5.9%), wetland from (8.24% to 7.9%), tree plantation from (4.87% to 3.3%). The changes threaten the environment and quality of life of people. Therefore, there is need to take critical and practical measures to regulate land use and landcover changes and conserve natural resources in Butambala District